THE USE OF PICTORIAL MEDIA TO IMPROVE STUDENTS’ SPEAKING AND WRITING SKILLS - R Andi Ahmad Gunadi; Nidar Yusuf; Aswir Aswir (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2018)
Media learning in the form of pictorial media can be utilized optimally to improve students’ speaking and writing skills. Speaking skill, as the first productive skill, is regarded as an oral spoken process for expressingthoughts and feelings, reflecting on experiences, and sharing information. On the other hand, as the second productive skill, writing refers to student’s skills in expressing ideas or messages through written form. This paper has objectives: 1). knowing students' speaking and writing skills; 2). utilizing pictorial media to improve students' speaking and writing skills. A descriptive qualitative research method is employed with 22 respondents from Grade 1 SDN Iwul 01 Parung, Bogor. The data are collected by observation, group discussions, interviews, and research instruments. The pictorial media are made in 2 shapes, namely the pictorial of the dots and the picture intact. The results of research: 1). Student speaking skills: the pictorial media are made in the form ofdots, 14 or 64% of students are correct in the names of animals and fruit plants; benefits of animals and fruit; where animals live and vitamins contained in the fruit. 2). Student writing skills: the pictorial media are made in the form of intact pictorials, 18 or 82% of students are correct in writing the names of animals and fruit plants; benefits of animals and fruit; where animals live and vitamins contained in the fruit. In conclusion, by utilizing the media, the learning process became more interesting, the subject matter was presented clearly. Keywords: learning media, pictorial media, speaking and writing skills